2002
DOI: 10.1159/000066516
|View full text |Cite
|
Sign up to set email alerts
|

Combined Intrapleural and Intravenous Chemotherapy, and Pulmonary Irradiation, for Treatment of Patients with Lung Cancer Presenting with Malignant Pleural Effusion

Abstract: Objectives: Patients with non-small-cell lung cancer (NSCLC) and malignant pleural effusion (MPE) are difficult to manage clinically and have a short life expectancy. In this pilot study, we designed a protocol of combined intrapleural (i.p.) and intravenous (i.v.) chemotherapy and pulmonary irradiation to enhance local as well as systemic control of the disease. Methods: From April 1998 to April 2000, 27 patients with NSCLC and symptomatic MPE were eligible for the study. Patients received pre-radiation chemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The present standard treatment is evacuation of the pleural fluid followed by intravenous or intrapleural chemotherapy [7]. However, it was found that not all patients were benefited from the chemotherapy, especially in patient with short overall survival time.…”
Section: Introductionmentioning
confidence: 99%
“…The present standard treatment is evacuation of the pleural fluid followed by intravenous or intrapleural chemotherapy [7]. However, it was found that not all patients were benefited from the chemotherapy, especially in patient with short overall survival time.…”
Section: Introductionmentioning
confidence: 99%
“…For NSCLC patients with MPE, the goals of treatment are to prolong survival and control the volume of pleural effusion [17][18][19]. We had hoped to find some biological predictors of incipient MPE so that we could use agents to block it.…”
Section: Introductionmentioning
confidence: 99%
“…Su et al [17] reported a more extensive combination therapy approach wherein 27 patients with MPE secondary to bronchogenic carcinoma received sequential treatment with IP cisplatin followed by intravenous gemcitabine, thoracic irradiation, and intravenous docetaxel. The overall response rate was 55% with 7% CR.…”
Section: Ip Chemotherapymentioning
confidence: 99%
“…The overall response rate was 55% with 7% CR. Remarkably, only 2 of 27 patients experienced recurrence of pleural effusion, and the 1-year survival was 63% [17]. To ascertain whether IP chemotherapy actually had an effect on malignant cells in the pleural space, Matsuzaki et al [18] resected primary pulmonary adenocarcinoma in 11 consecutive patients with pleural dissemination and subsequently treated them with IP cisplatin.…”
Section: Ip Chemotherapymentioning
confidence: 99%